2015
DOI: 10.1080/0020739x.2014.997318
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative analysis of the relationship between an online homework system and student achievement in pre-calculus

Abstract: Supporting student success in entry-level mathematics courses at the undergraduate level has and continues to be a challenge. Recently we have seen an increased reliance on technological supports including software to supplement more traditional in-class instruction. In this paper, we explore the effects on student performance of the use of a computer software program to supplement instruction in an entry-level mathematics course at the undergraduate level, specifically, a pre-calculus course. Relying on data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 8 publications
1
11
0
1
Order By: Relevance
“…Furthermore, its role receives greater importance especially in content‐heavy curriculums (Ruohoniemi & Lindblom‐Ylänne, ) and large class sizes (Harfitt & Tsui, ). The study builds on existing research about the benefits that computer‐based homework offers to students, for example, immediate feedback and step‐by‐step scaffolding (Hauk, Powers, & Segalla, ; Mendicino, Razzaq, & Heffernan, ) as well as optimization of student learning (Babaali & Gonzalez, ; Kelly et al, ). In line with previous findings suggesting that use of mobile devices in teaching yielded higher achievement scores than conventional teaching in all subject areas (Tingir et al, ), our MBmLA approach improves student factual knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, its role receives greater importance especially in content‐heavy curriculums (Ruohoniemi & Lindblom‐Ylänne, ) and large class sizes (Harfitt & Tsui, ). The study builds on existing research about the benefits that computer‐based homework offers to students, for example, immediate feedback and step‐by‐step scaffolding (Hauk, Powers, & Segalla, ; Mendicino, Razzaq, & Heffernan, ) as well as optimization of student learning (Babaali & Gonzalez, ; Kelly et al, ). In line with previous findings suggesting that use of mobile devices in teaching yielded higher achievement scores than conventional teaching in all subject areas (Tingir et al, ), our MBmLA approach improves student factual knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Berry (2013) found that weekly online homework assignments were the single most effective of the active learning strategies investigated at improving student performance in an introductory geology class (enrollment ∼200). Richards-Babb et al (2011) found that online homework improved student performance in introductory chemistry (enrollment > 200), and Babaali and Gonzalez (2015) found it improved student performance in a pre-calculus course (enrollment ∼200). Therefore, the preponderance of evidence, including from this study, indicates that regular online homework assignments improve student performance in a variety of fields and in both large and small classes.…”
Section: Resultsmentioning
confidence: 99%
“…The performance of students using online homework systems has been compared by researchers in many fields, including chemistry (Richards‐Babb, Drelick, Henry, & Robertson‐Honecker, 2011), economics (Rhodes & Sarbaum, 2015), geology (Berry, 2013), mathematics (Babaali & Gonzalez, 2015; Roschelle, Feng, Murphy, & Mason, 2016), physics (Bonham et al., 2001; Cheng, Thacker, & Cardenas, 2004), and others. However, such studies have most often been conducted in large introductory classes that have hundreds of students enrolled and student access to the instructor may be limited due to the sheer number of students the instructors interact with.…”
Section: Introductionmentioning
confidence: 99%
“…En educación superior hay resultados positivos en el uso de estos sistemas en matemáticas generales de primer año (Lowe, 2015;Vasko et al, 2018), en cálculo (Babaali & Gonzalez, 2015;Figueroa-Canas & Sancho-Vinuesa, 2017) y estadística de primer año (Jonsdottir et al, 2017). En estas implementaciones se aprecia que los estudiantes tienen una mayor autonomía para decidir si utilizan o no estos sistemas.…”
Section: Impacto En Rendimientounclassified